KOMUNIKASI DALAM POLA ASUH ORANG TUA TERHADAP GAYA BELAJAR SISWA KELAS V SDN SUKAMUKTI - Rizki, Dede; Lestari, Wahyu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This research will describe about the meaning of a communication that is ini parenting of fifth grade students at Sukamukti Elementar School. The existence of this carried out research will find out the communication in parenting is very important for the enchantment of students, especially when in the world of education.Interpersonal relationships occur in the form of communication between parents and student through a process of socialization, from childhood to growing up. The success that can be raised in this research activity is that parents become aware of the types of parenting patterns and students are able to tecognise the style of learning process. When socializing students to succed in the school, parents will certain do practices such as doing homework together, attending students activities at school, giving students time to read.This study also discusses the factors that influence students attitudes, strategic to start communicating between parents and students. The many types of parenting styles and learning that exist, parents and students are able to adjust the needs that suit them. The use of the method in this study is descriptive qualitative, the researcher is directly involved when the data collection process uses observation, documentation, interviews, questionnaires involing 3 parents and 3 students of fifth grade Sukamukti Elementar School. The result of the study show that parenting created by good parents will lead to communication that is in harmony with th etype of parenting used.